The cortical computations underlying feedback control in vocal production. (August 2015) - Houde, John F; Chang, Edward F
Highlights: State feedback control (SFC) model is described for speech motor control. SFC explains auditory suppression/enhancement depending on motor predictions. SFC explains auditory-driven vocal compensation during feedback pertubation. Abstract : Recent neurophysiological studies of speaking are beginning to elucidate the neural mechanisms underlying auditory feedback processing during vocalizations. Here we review how research findings impact our state feedback control (SFC) model of speech motor control. We will discuss the evidence for cortical computations that compare incoming feedback with predictions derived from motor efference copy. We will also review observations from auditory feedback perturbation studies that demonstrate clear evidence for a state estimate correction process, which drives compensatory motor behavioral responses. While there is compelling support for cortical computations in the SFC model, there are still several outstanding questions that await resolution by future neural investigations.